Sudden cardiac death, arrhythmogenic cardiomyopathy and intercalated disc pathology due to reduced filamin C protein levels: a matter of life and death - Holtzhausen, Christian; Heil, Lorena; Klingel, Karin; Fox, Henrik; Gummert, Jan; Gärtner, Anna; Schmidt, Andreas; Krüger, Marcus; Kirfel, Gregor; Van Der Ven, Peter F.M.; Milting, Hendrik; Clemen, Christoph S.; et al. (Human Molecular Genetics, 2025)
Mutations in the human FLNC gene encoding filamin C (FLNc) cause a broad spectrum of sporadic and familial cardiomyopathies and myopathies. We report on the genetic, clinical, morphological and biochemical findings in a German family harboring an FLNC variant that leads to severe cardiac disease comprising sudden cardiac death and arrhythmogenic cardiomyopathy. Genetic analysis identified a novel heterozygous FLNC variant in exon 16 (NM_001458.4:c.2495_2498delAGTA, het; p.K832TfsX45) in i) the index patient suffering from dilated cardiomyopathy necessitating heart transplantation, ii) a son, who died from sudden cardiac death, iii) a second son, who survived an episode of sudden cardiac arrest and iv) a third son affected by isolated skeletal muscle myopathy. FLNc protein levels were markedly reduced in cardiac tissue obtained from the index patient, implying that the p.K832TfsX45 FLNc variant most probably caused nonsense-mediated decay of the corresponding mRNA. Morphological analysis of the diseased cardiac tissue revealed extensive fibrotic remodeling, and marked degenerative changes of the contractile apparatus of cardiomyocytes and severe structural alterations of intercalated discs. Connexin-43 signal intensity at intercalated discs was diminished and FLNc labelling of myofibrils was attenuated or even absent. Proteome analyses demonstrated complex alterations of extracellular matrix and intercalated disc proteins. Our findings demonstrate that this novel, truncating FLNC mutation likely leads to haploinsufficiency, thereby causing a deleterious sequence of degenerative changes of cardiac tissue with extensive fibrotic remodeling and intercalated disc pathology as the structural basis for FLNC-related cardiomyopathy with life-threatening cardiac arrhythmias.
CRIS-Team Scopus Importer:2025-04-18
Keywords: arrhythmogenic cardiomyopathy; filamin C/FLNC mutation; intercalated disc; proteome analysis; sudden cardiac death